PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO PISCOK LUMERKU - Chandriana Alfarizi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine the effect of price and service quality on consumer satisfaction at Toko Piscok Lumerku in Bintaro Sector 3, which operates in the food sector in South Tangerang City. The research approach used is quantitative with a total of 96 respondents. The sampling technique employed Rao Purba's formula. Data collection was carried out through a Consumer questionnaire using a Likert scale. The results of the validity test show that all indicators in the Price variable (X1), Service Quality (X2), and Consumer Satisfaction (Y) are valid with values above 0.8. The classical assumption test indicates that the data is normally distributed (Kolmogorov-Smirnov 0.313), there is no multicollinearity (tolerance 0.581 and VIF 1.722), no autocorrelation (Durbin-Watson 2.183), and no heteroscedasticity (scatter plot is randomly dispersed). Multiple linear regression analysis shows the equation Y = 3.399 + 0.204X1 + 0.632 X2. The results of the t-test indicate that price (t calculated = 7.669 > t table = 1.986) and service quality (t calculated = 11.495 > t table = 1.986) have a significant impact on customer satisfaction. The F test shows that price and service quality simultaneously have a significant effect on customer satisfaction (F calculated = 73.186 > F table = 65.32). The coefficient of determination (R²) value of 0.611 indicates that 61.1% of customer satisfaction is influenced by price and service quality.